The origin of the P-type conductivity for Cu and Ag-doped NiO: Density functional theory study. (December 2022) - Fan, S.W.; Yang, L.; Chen, Yu; Dou, Baoying
Abstract: NiO, as a promising transparent p-type semiconductor, was intensively studied in experiment. Due to the difference of fabrication methods and defects concentration, it is difficult to make meaningful comparisons. In this work, the performance for Cu and Ag-doped NiO is fully evaluated by using the density functional theory method. Electronic structures show Cu and Ag substituting Ni (labeled as CuNi and AgNi ) are deep acceptors, and the ionization energy ε(0/-) for CuNi and AgNi are much higher than 0.20 eV. Our studies show the p-type conductivity for Cu and Ag-doped NiO mainly stems from the coexistent Ni vacancies (labeled VNi ). The ionization energy ε(0/-) for CuNi (AgNi ) plus VNi are 0.086 (0.012) eV. Under O-rich condition, the compounds M2 O2 and M2 O (M = Cu and Ag) are promising dopants sources. We expect this work could promote the fundamental understanding of the p-type conductivity for nonstoichiometric NiO as well as the Cu and Ag-doped NiO. Graphical Abstract: ga1